The use of formalist techniques and semiotic analysis in depicting social media realities in 'budi pekerti': a study of cinematic composition and social commentary - Rizkitaa, Meira Rai; Supiarza, Hery; Pawitan, Zakiah (Institut Seni Indonesia Surakarta, 2024)
The film